2015
DOI: 10.3174/ajnr.a4468
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of High Relaxivity for Brain Tumor Imaging: Results of a Multicenter Intraindividual Crossover Comparison of Gadobenate Dimeglumine with Gadoterate Meglumine (The BENEFIT Study)

Abstract: BACKGROUND AND PURPOSE:Gadobenate dimeglumine (MultiHance) has higher r1 relaxivity than gadoterate meglumine (Dotarem) which may permit the use of lower doses for MR imaging applications. Our aim was to compare 0.1-and 0.05-mmol/kg body weight gadobenate with 0.1-mmol/kg body weight gadoterate for MR imaging assessment of brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Considering the current intense focus on gadolinium‐related safety issues such as nephrogenic systemic fibrosis (NSF) and the potential deposition of gadolinium in the brain and other tissues, any opportunity to minimize the dose of GBCA administered would be highly desirable, particularly for those patients requiring repeat examinations for therapy monitoring. In a recent multicentric intraindividual crossover study, Vaneckova et al demonstrated the diagnostic potential of gadobenate at 0.05 mmol/kg bw for contrast‐enhanced (CE) MRI of brain tumors; importantly, the contrast enhancement and imaging performance achieved were similar to those obtained with a full dose (0.1 mmol/kg bw) of the standard relaxivity agent gadoterate meglumine (Dotarem). In light of safety concerns and considering that most neuro‐oncological MRI protocols integrate both perfusion DSC and CE T 1 ‐weighted MRI, it would be of great interest to determine if reliable CBV quantification can be achieved with gadobenate at just 0.05 mmol/kg bw.…”
mentioning
confidence: 93%
“…Considering the current intense focus on gadolinium‐related safety issues such as nephrogenic systemic fibrosis (NSF) and the potential deposition of gadolinium in the brain and other tissues, any opportunity to minimize the dose of GBCA administered would be highly desirable, particularly for those patients requiring repeat examinations for therapy monitoring. In a recent multicentric intraindividual crossover study, Vaneckova et al demonstrated the diagnostic potential of gadobenate at 0.05 mmol/kg bw for contrast‐enhanced (CE) MRI of brain tumors; importantly, the contrast enhancement and imaging performance achieved were similar to those obtained with a full dose (0.1 mmol/kg bw) of the standard relaxivity agent gadoterate meglumine (Dotarem). In light of safety concerns and considering that most neuro‐oncological MRI protocols integrate both perfusion DSC and CE T 1 ‐weighted MRI, it would be of great interest to determine if reliable CBV quantification can be achieved with gadobenate at just 0.05 mmol/kg bw.…”
mentioning
confidence: 93%
“…Gadobenate dimeglumine (MultiHance; Bracco Diagnostics, Monroe, New Jersey) is an ionic open-chain, linear GBCA that differs fundamentally from gadopentetate and other extracellular GBCAs in having an aromatic substituent on the chelating molecule. 21 Unique properties conferred by this substituent include increased R1-relaxivity, 22 which permits the acquisition of diagnostically valid images with a reduced dose, 23 and liver-specificity, which permits gadobenate use for hepatobiliary-phase liver applications. 24 An additional benefit is increased molecular stability compared with gadopentetate, other linear agents, and certain macrocyclic agents.…”
mentioning
confidence: 99%
“…1 In the abstract, we concluded, "No meaningful differences were recorded between 0.05 mmol/kg gadobenate and 0.1 mmol/kg gadoterate." We understand from a statistical point of view that equivalence cannot be claimed if the test hypothesis is not prospectively defined as "noninferiority."…”
Section: Statistical Analysis and Sample Sizementioning
confidence: 98%
“…The study design and analysis described in our article 1 are similar to the methodology used in many previous intraindividual comparative studies. [2][3][4][5][6][7][8][9] The primary study end point was the overall diagnostic preference of each of 3 readers for one gadolinium-based contrast agent (GBCA) over the other.…”
Section: Statistical Analysis and Sample Sizementioning
confidence: 99%